Epidemiological trends and incidence prediction of lung cancer in China based on the Global Burden of Disease study 2019 - Li, Han; Zhao, Meng; Fei, Gaoqiang; Wang, Zemin; Wang, Shuai; Wei, Pingmin; Li, Wei (Frontiers in Medicine, 2022)
Lung cancer remains the most common malignancy in China. This study aims to provide scientific support for the prevention and treatment of lung cancer by analyzing the epidemiological trends of lung cancer in China from 1990 to 2019. Based on the global health exchange database (GHDx), joinpoint and age-period-cohort analyses were performed to explore the trend of lung cancer incidence and mortality rates from 1990 to 2019. According to incidence rates from 1990 to 2019, a model was constructed to predict the incidence rates in the next 5 years. In addition, changes in risk factors associated with lung cancer deaths were compared between 1990 and 2019 and between males and females in 2019. The results are as follows. The age-standardized incidence rates (ASIRs), and age-standardized death rates (ASDRs) of lung cancer among Chinese had overall upward trends from 1990 to 2019. The ASDRs of females and males in China decreased since 2010. Interestingly, from 2016 to 2019, the ASIRs and ASDRs of females rose significantly. The age-period-cohort model showed that the incidence and mortality rates of lung cancer in China increased with age, and the growth rate accelerated after 45 years old. After 2004, the relative risks of lung cancer incidence increased with the passage of the period. Also, after the 1950–1954 birth cohort, the risks of lung cancer incidence and death began to decrease. The autoregressive integrated moving average (ARIMA) model predicted that the incidence rates of lung cancer in China would continue to rise in the next 5 years. The top five risk factors for lung cancer deaths of both genders in 2019 were smoking, ambient particulate matter pollution, secondhand smoke, high fasting plasma glucose, and household air pollution from solid fuels. The above results provided precise clues for the prevention and treatment of lung cancer in China.